Dental caries treatment completed under general anesthesia among American Indian children in a northern plains tribal community. (14th April 2020) - Warren, John J.; Thrap, Steven; Starr, Delores
Abstract: Objectives: To assess the occurrence of treatment under general anesthesia (GA) for dental caries among American Indian (AI) children from a Northern Plains tribal community. Methods: As part of a follow‐up study of ECC, dental records for children age 6–8 years were evaluated. Descriptive statistics were generated, including the number of dental visits, extent of treatment, and whether the treatment was completed under GA. Results: Data were obtained from 95 dental records. The age of dental visits varied from 15 months to 8 years. Of the 95 children, 79 (83.2%) received dental treatment under GA at least once; 24 (25.2%) did so two or more times. The majority of the treatment involved extractions and placement of stainless steel crowns. Conclusions: A large number of AI children received dental treatment under GA; many did so multiple times. Given the high cost of this treatment, even modestly effective preventive strategies such as silver diamine fluoride could yield cost savings.